Principles of Religious Tolerance from the Perspective of Surah Al-An’ām [6]:108 and Its Relevance in the Indonesian Context - Anam, Masrul; Fanani, Mochammad Rizal; Afrizal El Adzim Syahputra (QOF, 2023)
QS. al-An'ām [6]:108 contains the prohibition of insulting and degrading the worship of other religions. The purpose of this prohibition is to prevent the polytheists from insulting Allah in return for the insults made by the Muslims. The content of this verse suggests several principles of tolerance that need to be known and practiced by a plural society. This paper aimed to examine the verse in the framework of thematic interpretation and its correlation with the principles of tolerance in the Indonesian context. This research is a library research using thematic interpretation method. The focus of the theme in this study was the principle of tolerance implied in QS. al-An'ām [6]:108 which is then associated with the Indonesian context. The author can conclude three principles of tolerance based on this verse; First, not to defame the worship of other religions. Second, recognizing the existence of other religions. Third, preaching with good words. In the context of Indonesia, which consists of a plural society, these three principles are very important to maintain the harmony of religious life in the midst of the onslaught of various intolerant individuals and groups.